2001
DOI: 10.3109/10428190109064611
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Presentation of Hodgkin's Disease Mimicking Inflammatory Bowel Disease

Abstract: A case of a 32-years old man with a long lasting history of inflammatory bowel disease (IBD) is described. He was treated in the past with adequate medical therapy with considerable improvement of the symptoms. However, after the resolution of the last episode of abdominal pain and diarrhoea, because of multiple protruding masses and sub-stenotic regions found during a colonoscopy, the patient underwent a right enlarged hemicolectomy with jejunal resection. During the surgical procedure 16 enlarged lymphnodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…As per American Cancer Society’s estimates for HL in the United States, the 5-year and 10-year survival rates reached 85% and 80%, respectively [11]. However atypical presentations continue to pose a challenge [2,12]. …”
Section: Introductionmentioning
confidence: 99%
“…As per American Cancer Society’s estimates for HL in the United States, the 5-year and 10-year survival rates reached 85% and 80%, respectively [11]. However atypical presentations continue to pose a challenge [2,12]. …”
Section: Introductionmentioning
confidence: 99%
“…Primary GI HL involving the bowel has been associated with inflammatory bowel disease (IBD) in several case reports [9][10][11][12]. Kumar et al reported 4 cases of GI HL with concurrent EBV infection, with two of the cases occurring in patients with Crohn's disease.…”
Section: An Unusual Presentation Of Liver Failure In a Patient With Pmentioning
confidence: 99%
“…There are abundant reports of lymphoma of the gastro-intestinal tract mimicking presentations of Crohn's disease (Kashi et al, 2010, Kang et al, 2007, Hurlstone, 2002, Jouini et al, 2001, Vincenzi et al, 2001, Camera et al, 1997, Maaravi et al, 1993, Scully et al, 1993. Medline cited publications regarding lymphoma risk in IBD patients since 1950.…”
Section: Presentation Of Lymphoma In Ibdmentioning
confidence: 99%